Frequency‐Modulation‐Enhanced Ground‐State Cooling of Coupled Mechanical Resonators. Issue 11 (2nd September 2019) - Guan, Si‐Yu; Wang, Dong‐Yang; Bai, Cheng‐Hua; Yang, Jun‐Ya; Gao, Xiao‐Yuan; Zhu, Ai‐Dong; Wang, Hong‐Fu
Abstract: The coupled mechanical resonators (MRs) are the prominent candidate for studying macroscopic quantum coherence. The prerequisite for observing macroscopic mechanical coherence is cooling the MRs to their ground state. Here, a theoretical scheme is proposed for improving the cooling of two coupled MRs by imposing frequency modulation (FM) upon the system to suppress the Stokes heating processes. By the methods of covariance analysis and numerical simulations, it is demonstrated that the cooling of double MRs can be realized in both stable and unstable regions with high efficiency compared to the cooling without FM, even if in unresolved sideband (USB) regime. By modulating the parameters appropriately, the cooling efficiencies of two MRs can be flexibly adjusted. Abstract : The ground‐state cooling of two coupled mechanical resonators is investigated by imposing frequency modulations on the system. The results show that the simultaneous cooling of two mechanical resonators can be achieved not only in both stable and unstable regions, but also in unresolved sideband regime with high cooling efficiency.